(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Globally drug abuse has become a serious issue in the recent past. The abuse of cocaine, amphetamines and methamphetamines has been observed the most. Over the years, Chromatography and Spectroscopy have been the commonly applicable analytical methods for analysing drugs of abuse. Nowadays, these methods are being Drugs of abuse, Chromatography, characterization and further application to matter whose lowest functional organization is at nanoscale levels (Palit and Datta, 2010). The particles having dimension of 1 to 100 nanometres are referred as nanoparticles (NPs). These NPs have beenof great scientific interest as they provide with a link between large-sized materials and their atomic or molecular structures. Different nanodevices including sensors, tubes, chips, wires, etcare used in analysis purpose.